Functional Outcome and Quality of Life Following Total Hip Replacement Surgery - Regmi, Rabindra; Shrestha , Dipak; Shrestha, Rohit; Raj Kayastha , Sabik; Thapa , Jagadish; Sharma, Rajiv (Journal of Nepal Health Research Council, 2022)
Background: Total hip replacement surgeries are popular treatment modality for degenerative and traumatic hip condition which provides high degree of patient satisfaction and are mainly described in literatures among patient residing in western world. However activities of daily living of people in hilly area of developing country are different from western country but there are paucity of literature describing outcome of these people.Methods: Retrospective observational study was carried out in a university teaching hospital in Nepal. Patients residing in hilly region of Nepal who underwent total joint replacement of hip joint between 2017 to 2019 AD were included in the study. The functional outcome was measured using Harris Hip Score and the quality of life was assessed using SF-12 Patient Questionnaire preoperatively , 3 months , 6 months and 1 year follow up.Results: More than two-thirds of the patients were male. The mean age group of patients was 45.71 years. The most common indication of surgery was avascular necrosis of femoral head. There was significant improvement in Harris Hip Score upto 6 months postoperatively. Quality of life including both physical and mental component of SF-12 improved significantly upto 6 months. Conclusions: Total hip replacement surgery significantly improves functional outcome and quality of life of patients residing in hilly region of Nepal. However, long term follow up still is request to find out effect of joint replacement in activities of daily living in these group of people.Keywords: Harris hip score; mental component summary scores; pain component summary scores; total hip replacement.